Торгівля сільськогосподарськими товарами в рамках Генеральної угоди з тарифів і торгівлі (ГАТТ 1947) - Духневич, Андрій Вікторович; Духневич, І.; Dukhnevych, А.; Dukhnevych, I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено теоретико-прикладне дослідження торгівлі сільськогосподарськими товарами в рамках Генеральної угоди з тарифів і торгівлі 1947, а також місце міжнародної торгівлі й форми її регулювання в міжнародному праві. Розглянуто питання підвищення рівня стандартів виробництва та управління в агропро- довольчому секторі. Істотний принцип ГАТТ полягає в проведенні політики щодо зниження та, можливо, повного скасування тарифів й інших заходів, використовуваних для захисту внутрішнього сільського господарства.The article is devoted to the theoretical study of the agricultural trade within the framework of the General Agreement on Tariffs and Trade (GATT 1947), and the place of the international trade and forms of its regulation in the international law. Legal acts, the role and importance of the international trade of agricultural products for modern international relations, its form of regulation are investigated. It is proved that Ukraine's accession to the WTO and the actual development of international trade shows that globalization and internationalization of world economic processes has one of its consequences as a gradual blurring the boundaries between borderline and the internal regulation of the international economic exchange. The one of its results is a gradual shift of the center of gravity of the regulation of international trade from the most favored to national mode. Issues of raising the production standards and management in the agricultural sector are considered.
The Agricultural Trade Within the Framework of the General Agreement on Tariffs and Trade (GATT 1947).
Keywords: СОТ; торгівля; ГАТТ / СОТ; держави – члени СОТ; гармонізація; правові норми СОТ; WTO; trade; GATT/WTO; WTO Member States; harmonization; WTO legal acts